Interrupted time-series analyses of routine vaccination program for elderly pneumonia patients in Japan; an ecological study using aggregated nationwide inpatient data - Koichi Kobayashi; Taisuke Jo; Wataru Mimura; Maho Suzukawa; Nobuharu Ohshima; Goh Tanaka; Manabu Akazawa; Hiroki Matsui; Kiyohide Fushimi; Hideo Yasunaga; Takahide Nagase; Hideaki Nagai (Taylor & Francis Group, 2021)
A national routine pneumococcal pneumonia immunization program started in Japan in 2014. It targeted the population aged ≥65 years and used a 23-valent pneumococcal polysaccharide vaccine; PPSV23. However, its effectiveness was not well defined because of the lack of a comprehensive database on the PPSV23 vaccination status of each subject. We used interrupted time-series analyses to assess the changes in the incidence and prognosis of elderly patients hospitalized for pneumonia before and after initiation of the program. First, we estimated the PPSV23 coverage rates in subjects aged ≥65 years based on the number of shipped PPSV23 syringes and the estimated population in each prefecture. The estimated coverage rates reached around 40% in 2014 for the 3 Tohoku prefectures, while those in the other prefectures remained below 20%. After the national routine immunization program started, the estimated coverage rate increased significantly in every prefecture and exceeded 40% in 2017. Next, we aggregated the data extracted from the Japanese Diagnosis Procedure Combination database from April 2011 through February 2017 for hospitalized pneumonia patients aged ≥65 years. The data included data from 655,746 patients, excluding those in the 3 Tohoku prefectures. Interrupted time-series analyses found no change in the incidence of hospitalized pneumonia patients and in-hospital mortality after the vaccination program, but there was a decrease in the in-hospital mortality of pneumonia patients with severe comorbidities defined by the modified Charlson comorbidity index. These results suggest an association between the vaccination program and an improved outcome in hospitalized elderly pneumonia patients with severe comorbidities in Japan.